HUBUNGAN INTOLERANCE OF UNCERTAINTY DAN PSYCHOLOGICAL DISTRESS PADA INDIVIDU YANG TERDAMPAK TIDAK LANGSUNG OLEH BENCANA HIDROMETEOROLOGIS DI DATARAN TINGGI ACEH - Rini Liana Dewi; Cut Aya Riadhah (Jurnal EMPATI, 2026)
This study aims to examine the relationship between intolerance of uncertainty (IU) and psychological distress among individuals indirectly affected by hydrometeorological disasters in the highlands of Aceh. The research employed a quantitative approach with a correlational design. Participants consisted of 121 adults residing in Central Aceh and Bener Meriah Regencies who experienced indirect impacts such as power outages, limited communication access, difficulty obtaining basic needs, and disruption of economic activities. Data were collected using the Intolerance of Uncertainty Scale–Short Form (IUS-12) and the Perceived Stress Scale (PSS-10), and analyzed using Spearman’s rho correlation test. The results indicated a significant positive relationship between intolerance of uncertainty and psychological distress (ρ = 0.480; p < 0.001), with a moderate correlation strength. These findings suggest that individuals with higher levels of intolerance toward uncertainty tend to experience greater psychological distress in post-disaster situations. Overall, the study emphasizes the importance of considering psychological factors in disaster management, particularly among individuals indirectly affected and facing prolonged uncertainty.